LITERATURE REVIEW : PENGARUH MANAJEMEN STRES KERJA TERHADAP KINERJAKARYAWAN - Nurul Altika; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
In the context of modern organizations, stress management has become an important aspect because of the increasing demands of work. Job stress that is not managed properly can affect employee performance and the temptation of organizational goals. This study uses the literature review method to collect the latest information about the effect of work stress management on employee performance. Through searching for information sources such as books, journals, and online publications, researchers select relevant and high-quality articles for analysis. The results of this literature review indicate that effective work stress management contributes to improving employee performance. The main findings include the effect of stress management on employee productivity, motivation, and well-being. Studies also emphasize the importance of the role of the organization in creating a work environment that supports effective work stress management. Several factors influence the effectiveness of work stress management including social support, work autonomy, recognition and appreciation, task lightening, and organizational justice. The research also revealed five related articles relevant to this topic, covering various aspects and strategies in work stress management. Through a better understanding of the factors that affect work stress and effective strategies, it is hoped that organizations can create a healthier and more productive work environment. This abstract contributes to the development of knowledge and understanding in the field of work stress management, as well as provides insight for practitioners, managers and researchers who are interested in improving employee performance through effective work stress management